Motivational Strategies for Reducing Oral Presentation Anxiety among EFL University Students: A Mixed-Methods Study (The International Journal of Language Studies (ISSN : 3078 - 2244), 2025)
One of the major factors that negatively influences the learning output of English as a Foreign Language (EFL) students, particularly in the case of public universities with restricted communicative practice opportunities, is still the anxiety connected with oral presentations. The combined qualitative and quantitative investigation investigates the causes of oral presentation anxiety in Vietnamese EFL learners and, at the same time, studies the role of motivational techniques in anxiety reduction and boosting of students’ confidence. Quantitative information was generated using questionnaires given to 187 undergraduate students at a public university, and qualitative information was obtained with the help of semi-structured interviews with 10 EFL teachers and observations made in the classroom. Based on these results, it shows that presentation anxiety in students is mainly connected with language limitations and fear of being negatively evaluated, and there are few available practice opportunities in large-group situations. As the research suggests, a number of motivational factors, including cooperative learning, positive reinforcement, and purposeful practice, are critical to reducing anxiety and increasing confidence in speaking. The research draws attention to pedagogical matters that can support positive class climates, as well as the promotion of student-centred pedagogy to improve oral presentation performance in EFL.
Keywords: EFL learners, mixed methods, motivational strategies, oral presentation anxiety, Vietnamese higher education